2020
DOI: 10.21521/mw.6356
|View full text |Cite
|
Sign up to set email alerts
|

Piglets produced by transfer of embryos obtained by in vitro fertilization of oocytes matured in vitro with thymosin: A case report

Abstract: The aim of the study was to examine the in vivo viability of in vitro-produced (IVP) porcine embryos obtained from oocytes matured with thymosin. The research material for this study consisted of immature pig oocytes obtained from ovaries after slaughter and ejaculated semen obtained from one boar. The immature oocytes were cultured in vitro until the metaphase II stage in a medium supplemented with thymosin (TMS). The presumptive zygotes obtained were cultured in vitro for 4-40 hours. The presumptive zygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Therefore, TMS supplementation into maturation medium had a positive effect on the quality of obtained blastocysts by limiting the occurrence of apoptosis. In our other studies, we demonstrated that in vivo survivability evaluation of embryos obtained from fertilized oocytes matured with TMS resulted in pregnancy in two recipients and the subsequent birth of 16 live piglets (Poniedziałek-Kempny et al, 2020).…”
Section: The Quality Of Blastocysts Obtained After In Vitro Fertilizamentioning
confidence: 79%
See 3 more Smart Citations
“…Therefore, TMS supplementation into maturation medium had a positive effect on the quality of obtained blastocysts by limiting the occurrence of apoptosis. In our other studies, we demonstrated that in vivo survivability evaluation of embryos obtained from fertilized oocytes matured with TMS resulted in pregnancy in two recipients and the subsequent birth of 16 live piglets (Poniedziałek-Kempny et al, 2020).…”
Section: The Quality Of Blastocysts Obtained After In Vitro Fertilizamentioning
confidence: 79%
“…Culture was carried out at 39 °C, 5% CO 2 and maximum humidity. The maturation medium was described in detail in previous study (Poniedziałek-Kempny et al, 2020). The oocytes were randomly divided into 3 groups: A.…”
Section: In Vitro Maturationmentioning
confidence: 99%
See 2 more Smart Citations
“…As we anticipated, we showed the stimulatory effect of vaspin (1 ng/mL) on nuclear oocyte maturation. The total time to undergo metaphase-II for porcine oocytes cultured in vitro is 44 h [32]. In our experiments, we checked the progress in oocyte maturation by counting the percentage of oocytes first in metaphase-I after 22 h of culture (percentage of oocytes in metaphase-I) and then at metaphase-II after 44 h. The positive effect of vaspin on oocyte maturation was confirmed by increases in P4 levels in the culture medium after 22 and 44 h of culture.…”
Section: Discussionmentioning
confidence: 99%